Novel Approaches Outside the Setting of Immunotherapy for the Treatment of Multiple Myeloma: The Case of Melflufen, Venetoclax, and Selinexor - Sgherza, Nicola; Curci, Paola; Rizzi, Rita; Musto, Pellegrino (Frontiers in Oncology, 2021)
Although the survival rate of patients with multiple myeloma has significantly improved in the last years thanks to the introduction of various classes of new drugs, such as proteasome inhibitors, immunomodulatory agents and monoclonal antibodies, the vast majority of these subjects relapse with a more aggressive disease, due to the acquisition of further genetic alterations that may cause resistance to current salvage therapies. The treatment of these often “triple” (or even more) refractory patients remains challenging and alternative approaches are required to overcome the onset of that resistance. Immunotherapies with novel monoclonal, drug-conjugated or bi-specific antibodies, as well as the use of CAR-T cells, have been recently developed and are currently investigated. However, other, non immunologic, therapeutic regimens based on melfluflen, venetoclax or selinexor, three molecules with new mechanisms of action, have also shown promising results in the setting of relapsed/refractory myeloma. Here we report the most recent literature data regarding these three drugs, focusing on their efficacy and safety in multiple myeloma.